2015
DOI: 10.2340/16501977-1993
|View full text |Cite
|
Sign up to set email alerts
|

Capturing step counts at slow walking speeds in older adults: Comparison of ankle and waist placement of measuring device

Abstract: The Fitbit One can accurately capture steps at slow speeds when placed at the ankle and thus may be appropriate for capturing physical activity in slow-walking older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 28 publications
3
69
1
Order By: Relevance
“…Step counts for adults have been observed as valid, although Fitbit One devices tend to be inaccurate for measuring distance [13] and moderate-to-vigorous physical activity [10]. When placed at the ankle, Fitbit One has been observed to provide valid step counts of older adults at slow speeds [11]. Storm et al and Diaz et al found that Fitbit One underestimated step counts during treadmill walking and running [9, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Step counts for adults have been observed as valid, although Fitbit One devices tend to be inaccurate for measuring distance [13] and moderate-to-vigorous physical activity [10]. When placed at the ankle, Fitbit One has been observed to provide valid step counts of older adults at slow speeds [11]. Storm et al and Diaz et al found that Fitbit One underestimated step counts during treadmill walking and running [9, 12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, [191] shows that a Fitbit ® attached to the hip accurately tracks step-counting among healthy community-dwelling older adults, and it was reported in [192] that the Fitbit ® may be more accurate for step-counting at slow walking speed when attached on the ankle rather than on the waist. A similar comparison among three trackers has been carried out in [193] taking into account a waist and wrist positioning, resulting in high accuracy at slow speed with a sensor attached at the waist.…”
Section: Wearables For Senior Citizens: Related Work and Limitationsmentioning
confidence: 99%
“…The inaccuracy of the monitor when placed at the hip while walking slowly is a significant limitation considering that many individuals with disabilities, including those with poststroke hemiparesis, have a self‐selected gait speed under 0.8 m/s . The error rate of the evaluated monitor tested with short distances (15 m) and in a straight‐ahead direction became acceptable (<10%) for speeds as slow as 0.4 m/s when the device was placed at the right ankle in older healthy adults or at the nonparetic ankle in poststroke individuals . This observation was recently replicated in a clinical context.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In this context, one activity monitor has received particular attention. When the evaluated device is placed at the hip (as recommended by the manufacturer) in older healthy individuals walking slower than 0.8 m/s, its step error rate is higher than 10% 13 (ie, arbitrary threshold used previously and considered acceptable 14 ). The inaccuracy of the monitor when placed at the hip while walking slowly is a significant limitation considering that many individuals with disabilities, including those with poststroke hemiparesis, have a self-selected gait speed under 0.8 m/s.…”
Section: Introductionmentioning
confidence: 99%